2018
DOI: 10.4172/2155-9600.1000744
|View full text |Cite
|
Sign up to set email alerts
|

Production And Quality Evaluation Of Biscuit Incorporated With Fish Fillet Protein Concentrate

Abstract: This research was aimed to evaluate the physico-chemical and nutritional qualities of biscuit produced from sturgeon fillet protein concentrate (SFPC), based on gross chemical composition, effects of SFPC incorporation, and storage stability for six months. SFPC was used in production of biscuits by replacing low gluten wheat flour by 5%, 7% and 10% to ensure the quality and acceptability of the biscuit. The obtained results for biscuits fortified with SFPC revealed that the nutritional and proximate compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
(71 reference statements)
2
12
0
2
Order By: Relevance
“…The results of this study were in corroboration with the previous findings of Arise et al (2014). The result of present study was also in line with the previous findings of Abraha et al (2018) who observed the declining pattern of pH in biscuits prepared by fortification of fish fillet protein concentrate. The values of pH declining were similar with the diminution in pH values of energy bars samples found in the present study…”
Section: Resultssupporting
confidence: 93%
“…The results of this study were in corroboration with the previous findings of Arise et al (2014). The result of present study was also in line with the previous findings of Abraha et al (2018) who observed the declining pattern of pH in biscuits prepared by fortification of fish fillet protein concentrate. The values of pH declining were similar with the diminution in pH values of energy bars samples found in the present study…”
Section: Resultssupporting
confidence: 93%
“…Several factors have been reported to affect color changes on the product surface, amino acids, ingredients, temperature, air velocity, humidity and heat transfer into the sample. (Abraha et al, 2018); this has proven for example by Lund & Ray (2017), who found that the amount of FPC and the lack of baking temperature will cause a brownish discoloration. In this research, the effect of treatments on color can be seen FIGURE 8 for those who wish a clearer observation.…”
Section: Resultsmentioning
confidence: 94%
“…It was dried at 50 °C for 3.5 h till it was completely moisture free. The dried FPC was pulverised in a mixer grinder, packed in LDPE bags and stored at −20 °C for further use (Abraha et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Fish protein is highly nutritious and is a good source of essential amino acids such as lysine compared to cereals and other plant‐based proteins (Mohamed et al ., 2014; Abraha et al ., 2018; Mori et al ., 2020). Fish powder is a product of fish processing and represents a cheap source of high‐quality nutrients that can be utilised in the human diet (de Oliveira et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation